A Portfolio Approach to Estimating the Average Correlation Coefficient for the Constant Correlation Model - ANEJA, YASH P.; CHANDRA, RAMESH; GUNAY, ERDAL (Journal of Finance, 1989)
ABSTRACT This paper presents a portfolio approach to estimating the average correlation coefficient of a group of stocks which are considered for portfolio analysis. The average correlation coefficient has been shown to produce a better estimate of the future correlation matrix than individual pairwise correlations. The advantage of the approach described here is that it does not require the estimation of pairwise correlations for estimating their average.